Hummingbird pollination and the diversification of angiosperms: an old and successful association in Gesneriaceae. Issue 1852 (5th April 2017) - Serrano-Serrano, Martha Liliana; Rolland, Jonathan; Clark, John L.; Salamin, Nicolas; Perret, Mathieu
Abstract : The effects of specific functional groups of pollinators in the diversification of angiosperms are still to be elucidated. We investigated whether the pollination shifts or the specific association with hummingbirds affected the diversification of a highly diverse angiosperm lineage in the Neotropics. We reconstructed a phylogeny of 583 species from the Gesneriaceae family and detected diversification shifts through time, inferred the timing and amount of transitions among pollinator functional groups, and tested the association between hummingbird pollination and speciation and extinction rates. We identified a high frequency of pollinator transitions, including reversals to insect pollination. Diversification rates of the group increased through time since 25 Ma, coinciding with the evolution of hummingbird-adapted flowers and the arrival of hummingbirds in South America. We showed that plants pollinated by hummingbirds have a twofold higher speciation rate compared with plants pollinated by insects, and that transitions among functional groups of pollinators had little impact on the diversification process. We demonstrated that floral specialization on hummingbirds for pollination has triggered rapid diversification in the Gesneriaceae family since the Early Miocene, and that it represents one of the oldest identified plant–hummingbird associations. Biotic drivers of plant diversification in the Neotropics could be more related to this specific type of pollinator (hummingbirds) than to shifts among different functional groups of pollinators.